Role of nuclear receptor PXR in immune cells and inflammatory diseases - Sun, Le; Sun, Zhenzhen; Wang, Qian; Zhang, Yue; Jia, Zhanjun (Frontiers in Immunology, 2022)
Pregnane X receptor (PXR, NR1I2), a prototypical member of the nuclear receptor superfamily, has been implicated in various processes including metabolism, immune response, and inflammation. The immune system is made up of many interdependent parts, including lymphoid organs, cells, and cytokines, which play important roles in identifying, repelling, and eliminating pathogens and other foreign chemicals. An impaired immune system could contribute to various physical dysfunction, including severe infections, allergic diseases, autoimmune disorders, and other inflammatory diseases. Recent studies revealed the involvement of PXR in the pathogenesis of immune disorders and inflammatory responses. Thus, the aim of this work is to review and discuss the advances in research associated with PXR on immunity and inflammatory diseases and to provide insights into the development of therapeutic interventions of immune disorders and inflammatory diseases by targeting PXR.